Peran Efikasi Diri Dalam Memediasi Pengaruh Pengenalan Lapangan Persekolahan (PLP) dan Persepsi Profesi Guru Terhadap Minat Menjadi Guru Akuntansi - masrotin, Masrotin; Wahjudi, Eko (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Education Workforce Education Institutions (LPTK) is institutions that produce graduates to be a teacher. But not all students have an interest become a teacher, because growing interest is influenced by many factors. Several factors that are throught to influence growing interest in becoming an accounting teacher is School Field Introduction (PLP), teacher profession perceptions and self-efficacy. The purpose of study to find out self-efficacy as mediation to impact of School Field Introduction (PLP) and teacher profession perceptions on the interest become an accounting teacher. Quantitative research type. The population is active student from department of accounting education 2017, Universitas Negeri Surabaya a total of 96 students with saturated sampling technique. The data collection using a questionnaire. The data analysis method used is SEM-PLS. The acquisition proves 1) PLP has a positive significant effect the interest become an accounting teacher, 2) teacher profession perception has a positive significant effect the interest become an accounting teacher, 3) PLP has a positive significant effect the self-efficacy, 4) teacher profession perception has a positive significant effect the self-efficacy, 5) self-efficacy has a positive significant effect the interest become an accounting teacher, 6) PLP towards the interest become an accounting teacher through self-efficacy, 7) teacher profession perception towards the interest become an accounting teacher through self-efficacy.